(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2013)
Insurance is one of effective high-impact activities in the economic and social aspects of development and that the insurance companies after the creation of stability, balance and support other sectors. The insurance of financial institutions with economic and social importance has an impact on the development and help shoulder the burden of risk and distribution. And measuring Indicators of service and cost her help in evaluating the performance and activity of insurance, and the study of sectors needed by society, institutions and individuals and development of the company. Covering all aspects of life and activity. In this study will focus on the insurance sector in the field of car accidents and so plentiful and their problems and damages and losses that may afflict a third person. And has been selected the National Insurance Company being the leading company in the field of insurance. Therefore been selected as a sample for the study was reached several Indicators and conclusions that can be adopted in the development of insurance and measured service costs.